Co-sensitization between legumes is frequently seen, but variable and not always clinically relevant - Smits, Mark; Verhoeckx, Kitty; Knulst, André; Welsing, Paco; de Jong, Aard; Gaspari, Marco; Ehlers, Anna; Verhoeff, Paulien; Houben, Geert; Le, Thuy-My (Frontiers in Allergy, 2023)
Background Food allergy to peanut and soybean, both legumes, is highly prevalent. The consumption of other legumes and legume protein isolates, some of which may be considered novel foods, is increasing. This may lead to an increase in sensitization and allergy and may pose a risk for legume-allergic (e.g. peanut and soybean) patients due to cross-reactivity. Objective This study investigated the frequency of co-sensitization and co-allergy between legumes and the role of different protein families. Methods Six legume-allergic patient groups were included: peanut (n = 30), soybean (n = 30), lupine (n = 30), green pea (n = 30), lentil (n = 17), bean (n = 9). IgE binding to total extracts, protein fractions (7S/11S globulin, 2S albumin, albumin), and 16 individual proteins from 10 legumes (black lentil, blue lupine, chickpea, faba bean, green lentil, pea, peanut, soybean, white bean, and white lupine) was measured by line blot Results Co-sensitization varied from 36.7% to 100%. Mono-sensitization was only found in soybean (16.7%), peanut (10%), and green pea-allergic (3.3%) patients. A high frequency of co-sensitization between the 7S/11S globulin fractions of all 10 legumes and individual 7S and 11S globulins was observed. In peanut and soybean-allergic patients, co-allergies for other legumes were uncommon (≤16,7%), while in green pea, lupine, lentil, and bean-allergic patients co-allergy for peanut (64.7%–77.8%) or soybean (50%–64.7%) was frequently seen. Conclusion Co-sensitization between legumes was high, but generally not clinically relevant. Co-allergy to other legumes was not often seen in peanut- and soybean allergic patients. The 7S and 11S globulins were likely responsible for the observed co-sensitization.